18F-FDG PET for detecting metastases and synchronous primary malignancies in patients with oral and oropharyngeal cancer - Wallowy, P.; Diener, J.; Grünwald, F.; Kovács, A. F. (Nuklearmedizin - NuclearMedicine, 2009)
Aim: Assessment of the efficiency of 18F-FDGPET (PET) for the detection of distant metastases and synchronous primary malignancies in patients with oral and oropharyngeal squamous cell cancer (OOSCC). Patients, methods: Retrospective evaluation of PET studies of 422 patients with histologically confirmed OOSCC. 99 patients (23.5%) demonstrated a suspect distant finding of whom 84 could be interdisciplinary evaluated and consecutively confirmed or refuted by other diagnostic modalities or biopsy. Results: In 74 of 80 evaluable cases, PET showed the primary tumour (92.5%). 26/84 suspect distant lesions (31%) showed by means of PET were confirmed to be malignancies (mean SUV 3.96; range 1.4-9.37). Main sites were the lung, the upper aerodigestive tract, and the gastrointestinal system. In the other 58 cases (69%), where the suspect lesions were confirmed as benign, mean SUV was 2.65 (range 0.7–6.5) (difference statistically significant). The SUV above which every suspect finding was proven to be of malignant condition was 6.5 (specificity 100%, sensitivity 38%, accuracy 81%). Conclusion: PET may have an important role in initial staging and the detection of distant metastases and synchronous primary malignancies. Setting a SUV threshold for determining malignancies can support interpretation. In borderline cases, however, interdisciplinary evaluation by means of other diagnostic modalities remains crucial.
Keywords: 18F-FDG PET; oral and oropharyngeal squamous cell cancer; distant metastases; synchronous primary malignancies; standard uptake value